Finale : A Retrospective Review of Imperialist Japan's Defeat in 1945 - Editor-in-Chief: Zakharov M. V.; Translated by Skvirsky, David (Moscow Progress Publishers, 1972)
A Retrospective Review of Imperialist Japan's Defeat in 1945
Keywords: World War (1939-1945)